Unilateral Enlarged Vestibular Aqueduct Syndrome and Bilateral Endolymphatic Hydrops. (18th May 2017) - Ralli, Massimo; Nola, Giuseppe; Sparvoli, Luca; Ralli, Giovanni
Abstract : Enlarged vestibular aqueduct (EVA) syndrome is a common congenital inner ear malformation characterized by a vestibular aqueduct with a diameter larger than 1.5 mm, mixed or sensorineural hearing loss that ranges from mild to profound, and vestibular disorders that may be present with a range from mild imbalance to episodic objective vertigo. In our study, we present the case of a patient with unilateral enlarged vestibular aqueduct and bilateral endolymphatic hydrops (EH). EH was confirmed through anamnestic history and audiological exams; EVA was diagnosed using high-resolution CT scans and MRI images. Therapy included intratympanic infusion of corticosteroids with a significant hearing improvement, more evident in the ear contralateral to EVA. Although most probably unrelated, EVA and EH may present with similar symptoms and therefore the diagnostic workup should always include the proper steps to perform a correct diagnosis. Association between progression of hearing loss and head trauma in patients with a diagnosis of EVA syndrome is still uncertain; however, these individuals should be advised to avoid activities that increase intracranial pressure to prevent further hearing deterioration. Intratympanic treatment with steroids is a safe and well-tolerated procedure that has demonstrated its efficacy in hearing, tinnitus, and vertigo control in EH.